BEYOND DIALOGUE: INSTITUTIONAL GOVERNANCE OF RELIGIOUS DIVERSITY AND THE ROLE OF FKUB IN MANAGING INTERFAITH HARMONY IN BANDUNG - Dadan F Ramdhan; Muhamad Rizza; Asri Sulastri; Niela Agustin Hermawatie; Muhammad Hafidzin Maulana Rahman; Hilma Fatimatul Zahro (Harmoni, 2026)
Religious diversity in pluralistic urban societies presents significant governance challenges, requiring institutional mechanisms to sustain interfaith harmony and prevent social conflict. Although previous studies have examined interfaith dialogue and religious moderation, limited attention has been paid to how collaborative institutional governance manages religious diversity at the local level and to the empirical mechanisms by which local intermediary bodies translate normative tolerance into operational conflict prevention. This study aims to analyze the role of the Religious Harmony Forum (FKUB) within the institutional governance framework for maintaining interfaith harmony in Bandung, Indonesia. Employing a qualitative case study design, data were collected through semi-structured interviews with the Chairman of FKUB Bandung, the Acting Head of the Bandung City National Unity and Politics Agency (Kesbangpol), and the Head of the National Vigilance and Conflict Management Division, complemented by documentary analysis of official reports and conflict monitoring records. The data were analyzed using thematic analysis involving data reduction, coding, categorization, and interpretation. The findings reveal that religious harmony in Bandung is sustained through collaborative governance involving FKUB, Kesbangpol, religious organizations, community leaders, and local government agencies. FKUB functions not only as an interfaith dialogue forum but also as an institutional mediator facilitating communication, coordination, and conflict prevention. Most social tensions originate from socio-economic, socio-cultural, organizational, and political dynamics rather than theological differences. Building on these findings, the study conceptualizes religious harmony as an outcome of institutionalized social cohesion produced through collaborative governance, rather than as a passive absence of conflict. The study concludes that integrating institutional mediation, religious moderation, and cross-sector collaboration is essential for strengthening social resilience and sustaining long-term interfaith harmony in plural urban societies. Because the analysis draws on a single city and on institutional informants, the findings are presented as a transferable governance model rather than as a generalizable claim. Abstrak Keragaman agama dalam masyarakat perkotaan pluralistik menghadirkan tantangan tata kelola yang signifikan, membutuhkan mekanisme kelembagaan yang mempertahankan harmoni antaragama sekaligus mencegah konflik sosial. Meskipun penelitian sebelumnya telah meneliti dialog antaragama dan moderasi agama, perhatian terbatas telah diberikan pada bagaimana tata kelola kelembagaan kolaboratif mengelola keragaman agama di tingkat lokal, dan pada mekanisme empiris di mana badan perantara lokal mengubah toleransi normatif menjadi pencegahan konflik operasional. Penelitian ini bertujuan untuk menganalisis peran Forum Kerukunan Beragama (FKUB) dalam kerangka tata kelola kelembagaan untuk menjaga kerukunan antaragama di Bandung, Indonesia. Dengan menggunakan desain studi kasus kualitatif, data dikumpulkan melalui wawancara semi-terstruktur dengan Ketua FKUB Bandung, Plt. Kepala Badan Persatuan Nasional dan Politik (Kesbangpol) Kota Bandung, dan Kepala Divisi Kewaspadaan dan Penanggulangan Konflik Nasional, dilengkapi dengan analisis dokumenter laporan resmi dan catatan pemantauan konflik. Data dianalisis menggunakan analisis tematik yang melibatkan reduksi data, pengkodean, kategorisasi, dan interpretasi. Temuan tersebut mengungkapkan bahwa kerukunan beragama di Bandung dipertahankan melalui tata kelola kolaboratif yang melibatkan FKUB, Kesbangpol, organisasi keagamaan, tokoh masyarakat, serta instansi pemerintah daerah. FKUB berfungsi tidak hanya sebagai forum dialog antaragama tetapi juga sebagai mediator kelembagaan yang memfasilitasi komunikasi, koordinasi, dan pencegahan konflik. Sebagian besar ketegangan sosial berasal dari dinamika sosial-ekonomi, sosial-budaya, organisasi, dan politik daripada perbedaan teologis. Berdasarkan temuan ini, studi ini mengkonseptualisasikan kerukunan beragama sebagai hasil dari kohesi sosial yang dilembagakan yang dihasilkan melalui tata kelola kolaboratif, bukan sebagai ketiadaan konflik secara pasif. Studi ini menyimpulkan bahwa mengintegrasikan mediasi kelembagaan, moderasi agama, dan kolaborasi lintas sektor sangat penting untuk memperkuat ketahanan sosial serta mempertahankan harmoni antaragama jangka panjang dalam masyarakat perkotaan yang plural. Karena analisis ini mengacu pada satu kota dan satu informan institusional, temuan ini disajikan sebagai model tata kelola yang dapat ditransfer, bukan sebagai klaim yang dapat digeneralisasi.